Political economy of labor market policies for current labor market transformations in Europe - Fausto Favero (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2022)
Within the past decades, employment precariousness has emerged as an alarming phenomenon afflicting labor markets across Europe. While the spread of job insecurity can be traced to specific mechanisms and processes triggered by recent macroeconomic developments, evidence shows how mainstream practices in labor market policy hold some clear responsibilities. Policy prescriptions forwarded by the economic analysis of dominant politicaleconomic paradigms have been consistently prioritizing objectives of flexibility and competitiveness as a way to secure growth and employment, yet this strategy proved to be the source of lower quality and more uncertain jobs for wider shares of the workforce, with a higher incidence among the lower skilled. After having documented and further contextualized these labor market issues, the present research will investigate whether the unprecedented social challenges brought by the Covid-19 pandemic were met by the European Commission with an innovative approach to active labor market management. Our findings suggest that the proposal by the Commission of a policy strategy centered on upskilling and reskilling through training schemes might not break with past trends of precariousness. Specifically, as in the case of flexicurity, the attempt to achieve win-win solutions in different, and possibly contrasting, policy agendas - in this case the upskilling of highly qualified technicians and the reskilling and relocation of displaced workers - configures as an effective focus for political agreement, while numerous unaddressed barriers prevent the achievement of real change.
Keywords: J08; J24; J58; 330; Labor Market Policy; Europe; Policy Paradigm; Welfare-state; Precariousness; Neoliberalism; Flexicurity; Recovery